P2-3 How existentially distressed patients affect clinicians. (13th February 2023) - Dauchy, Sarah
Abstract : Patients' existential distress is a ' pain caused by extinction of the being and the meaning of the self ' (Murata & Morita 2006). It is associated with feelings of loss of autonomy, loss of dignity, loss of meaning and worth. Patients may also describe fear of death, hopelessness, helplessness, a sense of burdening others, a sense of isolation, sometime a feeling of betrayal. Although they should not be confused, existential distress is often associated with psychological distress. When the former refers to patient's personal values, beliefs, social and familial environment, the latter is more related to psychopathological mechanisms. However, both are deeply interconnected and sometimes hard to distinguish, for example in the wish to hasten death or in patients' requests for sedation (Guerrero-Torrelles 2017). Existential and psychological distress of palliative care patients contribute to the high levels of moral distress reported in palliative care providers (Maffoni 2019), alongside with difficult professional relationships and organisational constraints. Indeed, while responding to the physical distress makes it possible to rely on a collective (the palliative care team) and on objective (scientific) data, existential suffering mobilizes the carers in their individuality and reaches them in the most intimate dimension of their experiences, beliefs, or convictions. For the clinicians, being aware of this impact and recognizing their own feelings, emotions, representations are of a paramount importance to understand their possible effect on the patient-physician relationship and the therapeutic decisions. Moreover, while clinicians' distress is a subjective experience that negatively impacts quality of life and job satisfaction, it is also a biological one: for instance, short-term adjustment to the demands of the environment can create immediate stress response with increased sympathetic activity; long term adjustment with emotional exhaustion is linked with changes in cortisol metabolism (Fernandes-Sanchez 2018). Understanding how the distress of the patients and clinicians are intertwined is therefore essential. This presentation will also consider these patients-clinicians' interactions in the specific context of the wish to hasten death and of the medical aid in dying. For example, in France, where euthanasia is still illegal, French Law (so-called Claeys-Leonetti Law) allows the access to Continuous Sedation Until Death for end-of-life patients with refractory and unbearable psycho-existential distress. However, the process of diagnosing the refractory nature of psycho-existential distress remains ill defined; and the fact that it is unbearable has to be appreciated by the patient himself and must not reflect the doctor's limitations or exhaustion. Due to their own distress, clinicians may overestimate or underestimate the patient's suffering (Stiefel 2017); this has some potential ethical consequences on their ability to identify and respect patients' wills and expectations. Suppression of the clinicians' inner moves is neither possible nor necessary. Being aware of them is however, needed to make therapeutic choices that meet patients' expectations and needs as adequately as possible. Re-integrating these intrapersonal experiences in a collective dimension such as the one permitted by supervision groups and training in patient-physician relationship has also proven to be effective. Existential distress is a part of palliative care: being able to deal with this issue is a condition both of quality care and the good health of the professionals.